Development and validation of a gene expression test to identify hard-to-heal chronic venous leg ulcers. Issue 8 (16th May 2019) - Bosanquet, D C; Sanders, A J; Ruge, F; Lane, J; Morris, C A; Jiang, W G; Harding, K G
Abstract: Background: Chronic venous leg ulcers pose a significant burden to healthcare systems, and predicting wound healing is challenging. The aim of this study was to develop a genetic test to evaluate the propensity of a chronic ulcer to heal. Methods: Sequential refinement and testing of a gene expression signature was conducted using three distinct cohorts of human wound tissue. The expression of candidate genes was screened using a cohort of acute and chronic wound tissue and normal skin with quantitative transcript analysis. Genes showing significant expression differences were combined and examined, using receiver operating characteristic (ROC) curve analysis, in a controlled prospective study of patients with venous leg ulcers. A refined gene signature was evaluated using a prospective, blinded study of consecutive patients with venous ulcers. Results: The initial gene signature, comprising 25 genes, could identify the outcome (healing versus non-healing) of chronic venous leg ulcers (area under the curve (AUC) 0·84, 95 per cent c.i. 0·73 to 0·94). Subsequent refinement resulted in a final 14-gene signature (WD14), which performed equally well (AUC 0·88, 0·80 to 0·97). When examined in a prospective blinded study, the WD14 signature could also identify wounds likely to demonstrate signs of healing (AUC 0·73, 0·62 to 0·84). Conclusion: A gene signature can identify people with chronic venous leg ulcers that are unlikely to heal. Graphical Abstract: Genetic interrogation of wound-edge biopsies of chronic venous leg ulcers can be used to provide prognostic information on wound healing. Sequential refinement and validation, using three distinct patient cohorts, resulted in a 14-gene signature that was able to predict healing propensity for chronic venous leg ulcers. Identifies poor healers